Estudo da aplicação dos óleos do mucajá (Acrocomia aculeata (Jacq.) Lood. ex Mart) em membranas poliméricas - SANTANA, Laylton das Mercês (2022)
The mucajá (Acrocomia Aculeata (Jacq.) Lood. ex Mart) is an oleaginous palm tree, whose pulp and almond oils are extracted from the fruit, both with potential use in biofuels, cosmetics, functional foods, among others. The interaction of vegetable oils in chitosan-based biopolymers can enhance properties. In this sense, mucajá can also be used due to the properties present in its oils. The present work aims to extract oils from the mucajá fruit, characterize and study its application in biopolymer. The fruits were collected in the city of Curuçá-PA, and oils were extracted by solvent using hexane by the soxhlet method at the Laboratory of Amazonian Oils (LOA) of the Federal University of Pará (UFPA). The physicochemical characterization of the oils was carried out in accordance with the official standards of the American Oil Chemists' Society (AOCS) where the fatty acid composition, acid value, peroxide value, unsaponifiable matter and oxidative stability were determined. The biopolymer was synthesized based on chitosan and mucajá oil. The characterization of the biopolymer was performed using thermogravimetry (TG/DTG) and scanning electron microscopy (SEM) techniques. The study of yield as a function of extraction time, the highest result was 34.86% in the pulp and almond 16.40%. The fatty acid profile of the pulp oil predominantly consists of unsaturated fatty acids (82.71%). For almond oil, the opposite was observed, with a predominance of saturated fatty acids (67.04%). The acidity and peroxide indexes of the pulp oil were above the recommended by RDC nº 270/2005 of ANVISA. As for the unsaponifiable matter, the pulp oil had the highest percentage (1.08%). The oxidative stability, the pulp oil presented an induction period of 0.08 h and the almond 8.18 h. The study of the applicability of oils in biopolymer shows promise, since the synthesized biopolymer presented a homogeneous, stable and resistant structure.